2012
DOI: 10.1080/07315724.2012.10720438
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Herbs and Spices in Humans as Determined byex vivoInflammatory Suppression and DNA Strand Breaks

Abstract: DNA strand breaks and inflammatory biomarkers are a good functional measure of a food's bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
1
13
2
1
Order By: Relevance
“…The total amount used was high at 14 g but, again, palatability was not affected significantly. Unlike the findings of Percival et al ., the study reported increases in plasma antioxidant capacity suggesting that, as with Li et al ., the blend worked to improve antioxidant status and ultimately confer protection via this action. However, the increases were not consistent and appeared to be dependent on the hydrophilicity and lipophilicity of the antioxidant compounds, and the type of assay used.…”
Section: Culinary Herbs and Spicescontrasting
confidence: 85%
See 3 more Smart Citations
“…The total amount used was high at 14 g but, again, palatability was not affected significantly. Unlike the findings of Percival et al ., the study reported increases in plasma antioxidant capacity suggesting that, as with Li et al ., the blend worked to improve antioxidant status and ultimately confer protection via this action. However, the increases were not consistent and appeared to be dependent on the hydrophilicity and lipophilicity of the antioxidant compounds, and the type of assay used.…”
Section: Culinary Herbs and Spicescontrasting
confidence: 85%
“…In designing the study to include CHS-seasoned hamburger meat the authors recognised that CHS are normally consumed with other foods. Compared to the study discussed above, 11 the amount consumed in one take was high (11.3 g); however, palatability of the spiced hamburger was not significantly affected. Consumption of the spiced hamburger resulted in a trend to decreased plasma malondialdehyde over a 6 h period following consumption.…”
Section: Culinary Herbs and Spices Antioxidant And Anti-inflammatory contrasting
confidence: 67%
See 2 more Smart Citations
“…Η αντιοξειδωτική δράση του Δενδρολίβανου φαίνεται να αποδίδεται στην παρουσία ροσμαρινικού και καρνοσολικού οξέος στα εκχυλίσματά του (Pearson et al, 1997;Zeng et al, 2001). Η δράση επιβεβαιώνεται και για άλλα συστατικά βοτάνων τα οποία ανήκουν στα φλαβονοειδή, όπως η μυρισετίνη, η καμπφερόλη και τα μονοτερπένια θυμόλη και καρβακρόλη (Ha et al, 2014;Kulisic et al, 2007;Lian et al, 2008;Prieto et al, 2007;Singh et al, 2008 (Percival et al, 2012). Θετικά είναι και τα ευρήματα μελετών αναφορικά με την αντιαθηρογόνο δράση φαινολικών συστατικών σε ζωικά μοντέλα που σχετίζεται με την αντίσταση στην επαγόμενη οξείδωση της LDL ή/και του συνόλου των λιπιδίων του πλάσματος (Kurosawa et al, 2005;Yamakoshi et al, 1999).…”
Section: γενικά στοιχείαunclassified